Validation of the Mandarin Chinese Translation of the “Meaning of Life” in Patients with Hearing Loss or Tinnitus - Xie, Yufei; Wang, Yu; Pan, Tao; Tyler, Richard (Journal of the American Academy of Audiology, 2023)
Background There is an increasing need to evaluate the quality of life of individuals who are hearing impaired. However, most of the generic “quality of life” questionnaires do not include communication-related questions. Recently, a new “Meaning of Life” (MOL) questionnaire was developed to measure quality of life based on everyday issues, enabling a comprehensive evaluation of tinnitus patients and cochlear implant users. A Mandarin Chinese version of this questionnaire for the Mandarin-speaking population is needed. Many of the existing Mandarin Chinese questionnaires currently in use are not effectively assessing hearing-related conditions.Purpose We aimed to translate and validate the MOL questionnaire into Mandarin Chinese to make it applicable as a tool for measuring quality of life in patients with hearing loss or tinnitus.Research Design For this study, the original version of the MOL questionnaire was translated into the Mandarin Chinese language. A prospective cohort study was then performed on adults with hearing loss or tinnitus to preliminarily examine the reliability and validity of the Mandarin Chinese version.Study Sample A total of 206 Mandarin-speaking subjects with hearing loss or tinnitus were included in the study and divided into three groups according to their chief complaints: group B included patients suffering from both hearing loss and tinnitus (N = 113), group T contained patients with tinnitus alone (N = 49), and group H was composed of patients with hearing loss alone (N = 44).Data Collection and Analysis The Mandarin version of the MOL (C-MOL) was administered to the participants. The reliability of the C-MOL was evaluated using Cronbach's α and item total correlation coefficients. Exploratory factor analysis was performed to examine the relationships among the questions. Correlations between the patient characteristics and total scores were tested.Results The Cronbach's α coefficient of C-MOL was 0.921. Four factors were identified by exploratory factor analysis: (1) mental state and positive outlook; (2) friendship; (3) physical health; and (4) hearing and negative experience. The total scores of groups B, T, and H were 76.4 (standard deviation [SD] = 13.5), 81.3 (SD = 10.6), and 82.4 (SD = 12.5), respectively. The total score was correlated with the affected ears (r = 0.179, p < 0.05), age (r = 0.179, p < 0.05), hearing of the better ear (r = 0.188, p < 0.01), and educational background (r = 0.181, p < 0.01).Conclusion The Mandarin Chinese version of the MOL questionnaire showed good reliability. It can be used to quantify the quality of life of patients with hearing loss or tinnitus.
Keywords: hearing loss; tinnitus; quality of life; questionnaire; Mandarin population